What do unions do to temporary employment? - Andrea Salvatori (Institute for the Study of Labor (IZA), 2009)
In the EU, one in seven employees work on temporary contracts associated with lower pay and less training. Using workplace-level data from 21 countries, I show that, in contrast with previous evidence for the US, unionized workplaces are more likely to use temporary employment across Europe. To address the endogeneity of unions, I then use a British dataset and exploit variation over time and across occupations to control for workplace unobserved heterogeneity. This confirms that unions contribute to creating contract duality in the labour market and thus do not limit the ability of firms to adjust employment through flexible contracts.
Keywords: J41; J51; 330; Temporary employment; unions; panel data; Befristeter Arbeitsvertrag; Gewerkschaftspolitik; Betriebsvereinbarung; Gewerkschaftlicher Organisationsgrad; EU-Staaten; Großbritannien